Reflecting mirrors, East and West - Boccaccini, Enrico. (Leiden ; Boston)
xi, 314 sayfa
Keywords: “In Reflecting Mirrors, East and West Enrico Boccaccini sheds new light on Mirrors for Princes, the pre-modern genre of advice literature for rulers. A popular genre in the societies that emerged from the Late Antique oecumene, Mirrors for Princes are considered here, for the first time, as a transcultural phenomenon that challenges the dichotomy of the Orient and the Occident. Traditionally, the historiographic tradition has viewed 'European' and 'Middle Eastern' Mirrors as distinct and incommensurable. Analyzing the contents and discourses in four Mirrors, ostensibly separated by space, time and language, Enrico Boccaccini convincingly draws out the surprising continuities between these texts, while also showing how they are embedded in their own historical, literary and political context.“ --